2007
DOI: 10.1007/s10722-007-9248-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of the African hexaploid species Solanum scabrum Mill. and Solanum nigrum L. (Solanaceae)

Abstract: Two hexaploid species of Solanum sect. Solanum are present in Africa: Solanum scabrum and S. nigrum. Solanum scabrum is a widely cultivated species and is used as a leafy vegetable, as a source of medicine and as a source of ink dye. In previous studies a wide range of morphological diversity has been reported in this species and in some studies subspecies have been proposed. Subspecies are also recognized in S. nigrum. However, it has not been established whether or not the morphological differences are refle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 25 publications
4
24
0
2
Order By: Relevance
“…Results from seed protein studies (Edmonds and Glidewell 1977), as well as from more recent population genetic studies (e.g. Manoko 2007; Manoko et al 2008) support our morphological observations in finding no obvious patterns supporting infraspecific structure within particular variable species such as S. americanum , S. villosum and S. nigrum .…”
Section: Species Conceptssupporting
confidence: 83%
See 1 more Smart Citation
“…Results from seed protein studies (Edmonds and Glidewell 1977), as well as from more recent population genetic studies (e.g. Manoko 2007; Manoko et al 2008) support our morphological observations in finding no obvious patterns supporting infraspecific structure within particular variable species such as S. americanum , S. villosum and S. nigrum .…”
Section: Species Conceptssupporting
confidence: 83%
“…Manoko (2007; Manoko et al 2008) showed that this character did not correspond to monophyletic groups in his AFLP analyses of S. nigrum or S. villosum . Several species amongst the Old World black nightshades have both glandular and eglandular populations and individuals (e.g.…”
Section: Morphologymentioning
confidence: 97%
“…Although, the morphology of cultivated species is different from its wild ancestor and displays much greater diversity, in isozyme, DNA or other molecular markers the diversity remains almost the same (Lester and Daunay 2003). It can be concluded that hair characteristics have low taxonomic value at the subspecies level in section Solanum, confirming the results of Manoko et al (2008), Dehmer (2001) and Dehmer and Hammer (2004). The present study shows that S. nigrum, S. scabrum are closely related species, although this is supported by only moderate bootstrap value, it confirms our previous conclusions (Poczai et al 2008).…”
Section: ⎯⎯⎯⎯supporting
confidence: 90%
“…These differences could be attributed to breeding selection for different plant types. S. scabrum is the most intensively cultivated leafy vegetable in section Solanum, and as such has undergone selection by farmers (Manoko et al 2008). Presumably in this case, leaf size, stem wing and stem branching characters were the basis for selection.…”
Section: ⎯⎯⎯⎯mentioning
confidence: 99%
“…Among the Solanaceae, the monophyletic genus Solanum is the largest and most diverse one, with 1000 to 2000 species growing in all habitats from rainforest to deserts (Bohs, 2007;Bohs and Olmstead, 1999;Chung et al, 2006;Heiser and Anderson, 1999;Manoko et al, 2008). Species belonging to the Solanum genus show a remarkable agronomic importance, some of them are a basic part of diets in different parts of the world (i.e.…”
Section: Introductionmentioning
confidence: 99%